Rules, skills and autonomy: Pathological concepts of youth offending in Portuguese juvenile justice and custody - Zoettl, Peter Anton (International journal of law, crime and justice, 2018)
Based on research in a Youth Detention Centre, this article discusses the concept of autonomy within the treatment model of Portuguese juvenile justice. On the one hand, "dysfunctional" forms of autonomy are held responsible for a youth's offending tendencies, while, on the other hand, acquiring "proper" autonomy constitutes one of the principal objectives of a juvenile's confinement. Both, supposedly different, forms of autonomy are tied, respectively, to the absence or presence of discipline, rules and certain values in a youth's upbringing and socialization process. While this concept of autonomy could be linked to a number of scholarly theories on modern rationalities of crime governance, the article emphasizes the importance of paying attention to the "local criminologies" of the Portuguese law, judiciary and custody institutions, pointing to the persistence of a pathological model of youth offending within otherwise changing rationales.